2020
DOI: 10.1007/978-3-030-52200-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Practical Volume Estimation of Zonotopes by a New Annealing Schedule for Cooling Convex Bodies

Abstract: We study the problem of estimating the volume of convex polytopes, focusing on H-and V-polytopes, as well as zonotopes. Although a lot of effort is devoted to practical algorithms for H-polytopes there is no such method for the latter two representations. We propose a new, practical algorithm for all representations, which is faster than existing methods. It relies on Hit-and-Run sampling, and combines a new simulated annealing method with the Multiphase Monte Carlo (MMC) approach.Our method introduces the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For V-and Z-polytopes, the cost per step of BiW is comparable with that of CDHR. Moreover, it converges fast to the uniform distribution (Chalkis et al, 2019). The fact that all above walks are implemented in volesti enable us to empirically evaluate their mixing time using R (e.g., Figure 3).…”
Section: Mcmc Sampling and Geometric Random Walksmentioning
confidence: 99%
See 2 more Smart Citations
“…For V-and Z-polytopes, the cost per step of BiW is comparable with that of CDHR. Moreover, it converges fast to the uniform distribution (Chalkis et al, 2019). The fact that all above walks are implemented in volesti enable us to empirically evaluate their mixing time using R (e.g., Figure 3).…”
Section: Mcmc Sampling and Geometric Random Walksmentioning
confidence: 99%
“…For example, the asymptotic analysis by hides some large constants in the complexity, and in Lee and Vempala (2018), the step of the random walk used for sampling is too small to be an efficient choice in practice. Therefore, practical algorithms have been designed by relaxing the theoretical guarantees and applying new algorithmic and statistical techniques to perform efficiently while at the same time meeting the requirements for high accuracy results (Emiris and Fisikopoulos, 2014;Cousins and Vempala, 2016;Chalkis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ the annealing schedule from [11] to minimize k, without computing neither an enclosed r B n nor an enclosing ball RB n of S. We do so by probabilistically bounding each ratio of Eq. ( 9) in…”
Section: Volumementioning
confidence: 99%
“…For example, HR mixes after O(d 3 ) [29] steps for well rounded convex bodies and CDHR after a polynomial, in the diameter and the dimension, number of steps [27,34]. However, extended practical results have shown that both CDHR and HR converges after O(d 2 ) steps [9,12,18]. Billiard Walk (BW) [16] is a random walk that employs linear trajectories in a convex body with boundary reflections.…”
Section: Polytopes and Calls For Novel Practical Techniques To Samplementioning
confidence: 99%